Structure and dielectric dispersion in cubic-like 0.5K0.5Na0.5NbO3-0.5Na1/2Bi1/2TiO3 ceramic. (23rd June 2016) - Liu, Laijun; Knapp, Michael; Schmitt, Ljubomira Ana; Ehrenberg, Helmut; Fang, Liang; Fuess, Hartmut; Hoelzel, Markus; Hinterstein, Manuel
Abstract: The nature of the cubic-like state in the lead-free piezoelectric ceramics 0.5K0.5 Na0.5 NbO3 -0.5Na1/2 Bi1/2 TiO3 (KNN-50BNT) has been examined in detail by synchrotron x-ray diffraction (SD), selected-area electron diffraction (SAED), neutron diffraction (ND), and temperature-dependent dielectric characterization. The SD pattern of KNN-50BNT presents a pure perovskite structure with pseudocubic symmetry. However, superlattice reflections were observed by SAED and completely indexed by tetragonal symmetry with P 4 bm space group in ND pattern. The relaxor behavior of KNN-50BNT is compared with Pb-based and Ba-based relaxors and discussed in the framework of the Vogel-Fulcher law and the new glass model . The KNN-50BNT ceramic exhibits the strongest dielectric dispersion among them.